Framework for Culinary Entrepreneurship Learning System Integrating Pedagogy and Analytics - Perdana Suteja Putra; Grahita Prisca Brillianti; Kokom Komariah; Adhe Rizky Anugerah; Rhismah Tri Wahyuni; Faris Zulfan Ibrahim; Amar Al Haq; Azzuhra Muqaddasa Ginting; Harun Stephen Nafie (Universitas Islam Indragiri, 2026)
Entrepreneurship education in Indonesian vocational higher education remains constrained by theoretical approaches and generic learning management systems (LMS) that do not fully capture the multidimensional competencies required for entrepreneurial readiness. The culinary sector, which contributes nearly 42% of the creative economy’s GDP and is dominated by micro, small, and medium enterprises (MSMEs), highlights the urgent need for tailored pedagogical and technological solutions. This study proposes a conceptual framework for a culinary entrepreneurship learning information system, designed by integrating Deep Learning pedagogy, Innovation Canvas, and learning analytics. Drawing on preliminary findings from focus group discussions with practitioners and surveys of student competence, the research employed a conceptual design methodology guided by human-centered design principles. The resulting framework maps stakeholder needs into system components, including competency dashboards, e-portfolios, gamified features, and analytics-driven monitoring of five core entrepreneurial competencies: mentality, management, legality, branding, and networking. The framework demonstrates how reflective pedagogy can be operationalized into an information system architecture, bridging the gap between entrepreneurship education and digital innovation. Academically, it extends the literature on integrating pedagogy and information systems, while practically, it offers a replicable blueprint for higher education institutions seeking to enhance graduate employability and entrepreneurial readiness. The novelty of this study lies in integrating deep learning pedagogy, innovation canvas, and learning analytics into a unified conceptual framework for vocational entrepreneurship education—an approach not previously applied in the culinary education context. Future research should focus on prototyping, usability testing, and empirical validation to ensure the framework’s effectiveness and scalability.